2011
DOI: 10.1111/j.1464-5491.2011.03274.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous moderate‐intensity exercise with or without intermittent high‐intensity work: effects on acute and late glycaemia in athletes with Type 1 diabetes mellitus

Abstract: Although the decreases in glucose level during continuous moderate-intensity exercise and continuous moderate-intensity + intermittent high-intensity exercise are similar, the latter form of exercise protects against nocturnal hypoglycaemia in athletes with Type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
5
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 35 publications
(63 reference statements)
4
126
5
4
Order By: Relevance
“…During the process of peer review for this report, journal reviewers identified one extra study that fulfilled our inclusion criteria: Yardley et al [28]. Table 1 summarizes the main characteristics of the final ten publications [28][29][30][31][32][33][34][35][36][37] incorporated in this systematic review and meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the process of peer review for this report, journal reviewers identified one extra study that fulfilled our inclusion criteria: Yardley et al [28]. Table 1 summarizes the main characteristics of the final ten publications [28][29][30][31][32][33][34][35][36][37] incorporated in this systematic review and meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most articles (six of ten) presented glucose data as changes from baseline glycemia, either at the onset of the exercise session [29][30][31]33] or at some other reference instant: 90 min before the start of physical activity [35] or 20 min before the bout [36].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations